2022
DOI: 10.3389/fpsyg.2022.1005142
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the roles of fear and powerlessness in the relationship between perceived risk of the COVID-19 pandemic and information-avoidance behavior

Abstract: The COVID-19 has seriously impacted various aspects of the society on a global scale. However, it is still unclear how perceived risk influences epidemic information-avoidance behavior which generally helps us understand public information avoidance. This study aimed to assess the relationship between the perceived epidemic risk and information-avoidance behavior and the mediating role of fear and powerlessness during the COVID-19 pandemic in China. A total of 557 Chinese respondents with COVID-19 treated in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Although there has been literature on the powerlessness experienced by residents in COVID-19 pandemic (25)(26)(27), few studies have focused on this symptom of anti-COVID-19 medical staff. Our study found that powerlessness is also a symptom frequently reported by anti-COVID-19 medical staff when seeking psychological assistance services.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been literature on the powerlessness experienced by residents in COVID-19 pandemic (25)(26)(27), few studies have focused on this symptom of anti-COVID-19 medical staff. Our study found that powerlessness is also a symptom frequently reported by anti-COVID-19 medical staff when seeking psychological assistance services.…”
Section: Discussionmentioning
confidence: 99%